Estudo dos efeitos da melatonina sobre a função pulmonar e a qualidade do sono na asma - Campos, Francineide Lima (2004)
Disturbed sleep is common in asthma and impairs quality of life in these patients. Melatonin has sleep-inducing activity and reportedly affects smooth muscle tone and inflammation. The aim of this study was to evaluate the effect of melatonin on sleep in female patients with stable mild and moderate asthma. Twenty consecutive patients were recruited into the study. After a two-week run-in period, they were randomized to receive melatonin 3 mg (n= 10) or placebo for four weeks. Sleep quality and daytime somnolence were assessed by the Pittsburgh Sleep Quality Index and the Epworth Sleepiness Scale, respectively. Pulmonary function was assessed by spirometry. Use of relief medication, asthma symptoms and morning and evening peak expiratory flow rate (PEFR) were recorded daily. Melatonin treatment, but not placebo, significantly improved subjective quality of sleep (p = 0,034), sleep latency (p = 0.031), sleep duration (p = 0,034), sleep disturbances (p = 0,034), daytime dysfunction (p = 0,025) and subjective daytime somnolence (p = 0,028). No significant difference in asthma symptoms, use of relief medication and daily PEFR was found between the two groups. We conclude that melatonin can improve sleep in patients with asthma without significantly affecting pulmonary function or asthma symptoms. Further studies looking into long-term effects of melatonin on airway inflammation and bronchial hyperresponsiveness are needed before melatonin can be safely recommended in asthmatic patients.